Analisis Manajemen Risiko Proses Underwriting pada Asuransi Syariah : Studi Kasus PT Asuransi Jiwa Reliance Syariah - Rizky Syachlan Pratama; Mira Rahmi (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Underwriting is a vital process in Islamic insurance because underwriting is one of the factors for Islamic insurance companies to experience profits or losses. Risk management is an important part of sharia insurance in carrying out its operations. Good risk management allows sharia insurance companies to grow and provide profits. This study aims to analyze the underwriting risk management process at PT Asuransi Jiwa Reliance Syariah Unit based on POJK No.44/POJK.05/2020 with descriptive qualitative research methods. Data was collected by conducting interviews, observation and documentation. Data analysis techniques in this study used data reduction, data presentation, and drawing conclusions. The results of this study show that the application of risk management underwriting processes implemented by PT Asuransi Jiwa Reliance Unit Syariah has been going well, systematically and complies with POJK regulations No.44/POJK.05/2020, this is evidenced by the results of the OJK audit which shows no evaluation. as well as violations in the underwriting risk management process as well as the company's internal SOPs running well.